Forces at the anterior meniscus attachments strongly increase under dynamic knee joint loading - Seitz, Andreas Martin; Schall, Florian; Hacker, Steffen Paul; Drongelen, Stefan van; Wolf, Sebastian Immanuel; Dürselen, Lutz (The American journal of sports medicine, 2021)
Background:The anatomic appearance and biomechanical and clinical importance of the anterior meniscus roots are well described. However, little is known about the loads that act on these attachment structures under physiological joint loads and movements.Hypotheses:As compared with uniaxial loading conditions under static knee flexion angles or at very low flexion-extension speeds, more realistic continuous movement simulations in combination with physiological muscle force simulations lead to significantly higher anterior meniscus attachment forces. This increase is even more pronounced in combination with a longitudinal meniscal tear or after total medial meniscectomy.Study Design:Controlled laboratory study.Methods:A validated Oxford Rig?like knee simulator was used to perform a slow squat, a fast squat, and jump landing maneuvers on 9 cadaveric human knee joints, with and without muscle force simulation. The strains in the anterior medial and lateral meniscal periphery and the respective attachments were determined in 3 states: intact meniscus, medial longitudinal tear, and total medial meniscectomy. To determine the attachment forces, a subsequent in situ tensile test was performed.Results:Muscle force simulation resulted in a significant strain increase at the anterior meniscus attachments of up to 308% (P < .038) and the anterior meniscal periphery of up to 276%. This corresponded to significantly increased forces (P < .038) acting in the anteromedial attachment with a maximum force of 140 N, as determined during the jump landing simulation. Meniscus attachment strains and forces were significantly influenced (P = .008) by the longitudinal tear and meniscectomy during the drop jump simulation.Conclusion:Medial and lateral anterior meniscus attachment strains and forces were significantly increased with physiological muscle force simulation, corroborating our hypothesis. Therefore, in vitro tests applying uniaxial loads combined with static knee flexion angles or very low flexion-extension speeds appear to underestimate meniscus attachment forces.Clinical Relevance:The data of the present study might help to optimize the anchoring of meniscal allografts and artificial meniscal substitutes to the tibial plateau. Furthermore, this is the first in vitro study to indicate reasonable minimum stability requirements regarding the reattachment of torn anterior meniscus roots.